Mesophyll conductance to CO2 and leaf morphological characteristics under drought stress during Quercus ilex L. resprouting - Fleck, Isabel; Peña-Rojas, Karen; Aranda, Xavier (Annals of Forest Science, 2010)
• Quercus ilex L., the dominant species in Mediterranean forests and one with a great capacity for resprouting after disturbances, is threatened by the expected increase in ﬁre frequency and drought associated with climate change. • The aim of this study was to determine the contribution of photosynthesis limitants, especially mesophyll conductance (gmes ) during this species’ resprouting and under summer drought. • Resprouts showed 5.3-fold increased gmes and 3.8-fold increased stomatal conductance (gs ) at midday with respect to leaves of undisturbed individuals. With increased drought, structural changes (decreased density and increased thickness) in resprouts contributed to the observed higher photosynthesis and increased gmes . However, gmes only partially depended on leaf structure, and was also under physiological control. Resprouts also showed lower non-stomatal limitations (around 50% higher carboxylation velocity (Vc,max) and capacity for ribulose-1,5-bisphosphate regeneration (Jmax)). A signiﬁcant contribution of gmes to leaf carbon isotope discrimination values was observed. • gmes exhibits a dominant role in photosynthesis limitation in Q. ilex and is regulated by factors other than morphology. During resprouting after disturbances, greater capacity to withstand drought, as evidenced by higher gmes , gs and lower non-stomatal limitants, enables increased photosynthesis and rapid growth.
Keywords: carbon isotopic composition; leaf structure; mesophyll conductance; photosynthesis limitants; Quercus ilex

Photosynthesis, growth and structural characteristics of holm oak resprouts originated from plants grown under elevated CO2 - Aranda, Xavier; Agustí, Cristina; Joffre, Richard; Fleck, Isabel (Physiologia Plantarum, 2006)
The physiological characteristics of holm oak (Quercus ilex L.) resprouts originated from plants grown under current CO2 concentration (350 μl l−1) (A-resprouts) were compared with those of resprouts originated from plants grown under elevated CO2 (750 μl l−1) (E-resprouts). At their respective CO2 growth concentration, no differences were observed in photosynthesis and chlorophyll fluorescence parameters between the two kinds of resprout. E-resprouts appeared earlier and showed lower stomatal conductance, higher water-use efficiency and increased growth (higher leaf, stem and root biomass and increased height). Analyses of leaf chemical composition showed the effect of elevated [CO2] on structural polysaccharide (higher cellulose content), but no accumulation of total non-structural carbohydrate on area or dry weight basis was seen. Four months after appearance, downregulation of photosynthesis and electron transport components was observed in E-resprouts: lower photosynthetic capacity, photosystem II quantum efficiency, photochemical quenching of fluorescence and relative electron transport rate. Reduction in ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) activity, deduced from the maximum carboxylation velocity of RuBisCo, accounts for the observed acclimation. Increased susceptibility of photosynthetic apparatus to increasing irradiance was detected in E-resprouts.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CO2; Elevated CO2; Fluorescence (voyant); Growth; photosynthesis; Resprouts

Photosynthesis, growth and structural characteristics of holm oak resprouts originated from plants grown under elevated CO2 (Physiologia Plantarum, 2006)
The physiological characteristics of holm oak (Quercus ilex L.) resprouts originated from plants grown under current CO2 concentration (350 μl l−1) (A-resprouts) were compared with those of resprouts originated from plants grown under elevated CO2 (750 μl l−1) (E-resprouts). At their respective CO2 growth concentration, no differences were observed in photosynthesis and chlorophyll fluorescence parameters between the two kinds of resprout. E-resprouts appeared earlier and showed lower stomatal conductance, higher water-use efficiency and increased growth (higher leaf, stem and root biomass and increased height). Analyses of leaf chemical composition showed the effect of elevated [CO2] on structural polysaccharide (higher cellulose content), but no accumulation of total non-structural carbohydrate on area or dry weight basis was seen. Four months after appearance, downregulation of photosynthesis and electron transport components was observed in E-resprouts: lower photosynthetic capacity, photosystem II quantum efficiency, photochemical quenching of fluorescence and relative electron transport rate. Reduction in ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) activity, deduced from the maximum carboxylation velocity of RuBisCo, accounts for the observed acclimation. Increased susceptibility of photosynthetic apparatus to increasing irradiance was detected in E-resprouts.

Total antioxidant activity in Quercus ilex resprouts after fire - El Omari, Bouchra; Fleck, Isabel; Aranda, Xavier; Abadía, Anunciación; Cano, Antonio; Arnao, Marino B. (Plant Physiology and Biochemistry, 2003)
After ﬁre, holm oak (Quercus ilex L.) resprouts have a higher light availability and photosynthetic activity than control plants in intact vegetation. To assess the differences in protection between these plants, we determined, in two forests, changes in gas-exchange rates, chlorophyll ﬂuorescence parameters, chloroplast pigment content and total antioxidant activity (TAA) in different seasons, at different times of the day and in relation to leaf age. The end-point method used for TAA determination allowed the evaluation of the relative contribution of hydrophilic and lipophilic antioxidants in leaf extracts. High correlations were obtained between lipophilic TAA and certain chloroplast pigment content, the highest contribution being provided by b-carotene and the components of the xanthophyll cycle (zeaxanthin + antheraxanthin, violaxanthin). All leaves showed a much higher contribution (94–99%) of hydrophilic than lipophilic antioxidants to TAA. In summer, at midday, photosynthetic rates and TAA were higher in resprouts. In these plants, reduced xanthophyll-cycle participation (as shown by non-photochemical quenching (NPQ) and xanthophyll pool content) was compensated by an increased participation of hydrophilic antioxidants. No effect of time of day or plant age was observed. The results suggest that energy dissipation as heat, and detoxiﬁcation mechanisms contribute to the protective strategies of control plants and resprouts, albeit to a different extent.
Keywords: carotenoids; non-photochemical quenching; Quercus ilex; reactive oxygen species; Resprouts; total antioxidant activity

Total antioxidant activity in Quercus ilex resprouts after fire (Plant Physiology and Biochemistry, 2003)
After ﬁre, holm oak (Quercus ilex L.) resprouts have a higher light availability and photosynthetic activity than control plants in intact vegetation. To assess the differences in protection between these plants, we determined, in two forests, changes in gas-exchange rates, chlorophyll ﬂuorescence parameters, chloroplast pigment content and total antioxidant activity (TAA) in different seasons, at different times of the day and in relation to leaf age. The end-point method used for TAA determination allowed the evaluation of the relative contribution of hydrophilic and lipophilic antioxidants in leaf extracts. High correlations were obtained between lipophilic TAA and certain chloroplast pigment content, the highest contribution being provided by b-carotene and the components of the xanthophyll cycle (zeaxanthin + antheraxanthin, violaxanthin). All leaves showed a much higher contribution (94–99%) of hydrophilic than lipophilic antioxidants to TAA. In summer, at midday, photosynthetic rates and TAA were higher in resprouts. In these plants, reduced xanthophyll-cycle participation (as shown by non-photochemical quenching (NPQ) and xanthophyll pool content) was compensated by an increased participation of hydrophilic antioxidants. No effect of time of day or plant age was observed. The results suggest that energy dissipation as heat, and detoxiﬁcation mechanisms contribute to the protective strategies of control plants and resprouts, albeit to a different extent.